2011
DOI: 10.1111/j.1365-2494.2011.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofin situfreezing on soil net nitrogen mineralization and net nitrification in fertilized grassland of northern China

Abstract: Effects of soil freezing on nitrogen (N) mineralization have been the subject of increased attention in the ecological literature, though fewer studies have examined N mineralization responses to successive mild freezing, severe freezing and cyclic freeze–thaw events. Even less is known about relationships of responses to soil N status. This study measured soil N mineralization and nitrification in the field along an experimental N gradient in a grassland of northern China during the dormant season (October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…However, the results of the current study suggest that denitrification mainly contributed to the N 2 O emissions during freeze-thaw cycles [74]. The large amount of NO 3 -that accumulated during the lengthy winter [75] stimulated denitrification. In addition, the topsoil thawed first, but the deeper soil remained frozen and was not permeable to water.…”
Section: N 2 O Fluxmentioning
confidence: 50%
“…However, the results of the current study suggest that denitrification mainly contributed to the N 2 O emissions during freeze-thaw cycles [74]. The large amount of NO 3 -that accumulated during the lengthy winter [75] stimulated denitrification. In addition, the topsoil thawed first, but the deeper soil remained frozen and was not permeable to water.…”
Section: N 2 O Fluxmentioning
confidence: 50%
“…In contrast, lower temperatures (e.g. 10°C) exhibited inhibiting effects (Figure 1) due to lower microbial and enzyme activities [19], [41]. Grenon et al [42] also showed that most microbial metabolic rates are positively related to temperature.…”
Section: Discussionmentioning
confidence: 97%
“…Gilliam et al [18] suggested that mild freezing might inhibit N mineralizing microbes and stimulate N immobilizing groups. However, Zhang et al [19] demonstrated that mild freezing had few effects on N mineralization, while Gao et al [2] observed higher N mineralization rates in winter than in summer in a seasonal flooding wetland. Therefore, a better understanding of how variation of air temperature could affect N mineralization is urgently needed since the potential increase of the earth's surface temperature could be 1.8–4.0°C at the end of this century [20] .…”
Section: Introductionmentioning
confidence: 99%
“…1I). To our knowledge, there is no other study investigating gross N turnover in frozen soil, but Zhang et al (2011) reported significant net nitrification or net nitrate immobilization under frozen soil conditions for steppe sites of Duolun County, Inner Mongolia, in a Fig. 4.…”
Section: Contribution Of Seasons To Annual N Turnovermentioning
confidence: 99%